Rule of Law and Lawyers in Latin America - Rogelio Pérez-Perdomo (My University, 2016)
From the nineteenth century onward, lawyers have been the leading members of Latin American political elites. Nevertheless, Latin American countries have been plagued with caudillos and dictators, and lawyers have been these strongmen’s collaborators. The article explains the dissonance between the constitutionalism and legalism taught at the universities and the sordid political practices that resulted from the lack of independence of the legal profession: there was not a market for lawyers’ services, so lawyers depended on those who controlled the political apparatus. The situation started changing in the late twentieth century. During this recent period, lawyers and judges have shown more independence and have become active political players, using the law as an instrument for opposing arbitrary political practices. The new trend is explained not only by the increased awareness of the rule of law values but also by the existence of a market for legal services.